Evaluation of Entrepreneurial Intention among Vocational High School Students in the Context of Entrepreneurship Education Implementation in South Sulawesi - Suhaeb, Sutarsi; Ma’ruf Idris, Muh. (International Journal of Technology and Education Research, 2025)
This study aims to analyze the level of entrepreneurial intention of Vocational High School (SMK) students in South Sulawesi Province. Entrepreneurial intentions are an important indicator in measuring students' readiness and interest in entrepreneurship as one of the alternative career options after graduation. This research is motivated by the importance of entrepreneurship education in vocational schools in supporting the creation of new jobs and reducing the unemployment rate among vocational education graduates. The research method used is a descriptive quantitative approach. The sampling technique was carried out using multistage sampling through three stages, namely: (1) determination of the population of all state vocational schools in 24 districts/cities in South Sulawesi, (2) random selection of two districts/cities, namely Makassar City and Gowa Regency, and (3) purposively selection of each of three vocational schools based on the school's involvement in entrepreneurial activities through the School Production Unit (UPS). The number of respondents in this study was 275 students. Data was collected using a questionnaire instrument that measures the dimensions of entrepreneurial intention, including entrepreneurial interest, motivation, and readiness to start a business. Data analysis was carried out descriptively using frequency distribution. The results of the study show that the level of entrepreneurial intention of vocational school students in South Sulawesi Province is relatively high, with the majority of students showing a strong desire to be entrepreneurial after completing their education. No students were found in the low or very low category of entrepreneurial intentions. These findings indicate that entrepreneurship education in vocational schools, especially through entrepreneurial practice activities within UPS, has contributed positively to building an independent mindset, risk-taking courage, and students' confidence to become young entrepreneurs. This research makes a theoretical contribution to the development of literature on entrepreneurship education in the context of vocational education, as well as a practical contribution for education policymakers in designing learning programs that are oriented towards strengthening students' entrepreneurial spirit